Optimization of Visa Services through Information Technology at the South Jakarta Immigration Office Based on Immigration Law - Abigail Syaqiena Hadinagoro; Muhammad Imam Nasef (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2026)
The use of information technology in visa services can provide convenience; however, it also gives rise to various problems, as experienced at the South Jakarta Immigration Office, including ineffective mechanisms, technical disruptions, and the potential for identity falsification. The research problems addressed in this study concern how information technology is used in visa services at the South Jakarta Immigration Office based on Law Number 63 of 2024 in conjunction with Law Number 6 of 2011, as well as the obstacles encountered in the use of information technology in visa services at the South Jakarta Immigration Office. This study employs a normative research method with a descriptive approach. Data were collected through literature studies and interviews and analyzed qualitatively. The results indicate that visa services at the South Jakarta Immigration Office have implemented information technology through an online-based e-visa system as regulated in Law Number 63 of 2024 in conjunction with Law Number 6 of 2011. All visa application processes are conducted digitally and in real time. The obstacles encountered include internal constraints, such as discrepancies in uploaded data, system validation failures, and technical disruptions, as well as external constraints, including the risk of cyberattacks, potential data breaches, and low levels of users’ digital literacy. These obstacles have been addressed through improvements in technological infrastructure, strengthening of digital security, and the provision of online guidelines to ensure the continuity of optimal services. The Government is expected to enhance continuous evaluation of the electronic visa system.